SWELLING AND COMPRESSIBILITY CHARACTERISTICS OF SOIL - BENTONITE MIXTURES - Agus Setyo Muntohar (Institute of Research and Community Outreach - Petra Christian University, 2003)
Understanding characteristics of soil mixtures lead to increasing the confidence level before applying such materials in the field. The outcomes of this study can provide insight into the swelling and the compressibility behavior of soil – bentonite mixtures, between non-swelling materials and swelling materials. A simple swell and compression laboratory test has been conducted for the purposes of this study. The result of this study indicated that the existence of bentonite in the soil mixtures influence the swelling behavior, which follows a hyperbolic curve model. Amount and size of nonswelling fraction affected the swelling and compressibility.